Visualization of job availability based on text analytics localization approach - Mohamad Zamani, Nur Azmina; Kamaruddin, Norhaslinda; Rahman, Abdul Wahab; Saat, Nur Shahana; , (Universitas Ahmad Dahlan, 2019)
Rate of employment is a strong indicator of economic stability that relates to the services and products. One of the main factors that contributes to low rate employment is the mismatch between job seeker and the job requirement due to the limited analysis performed on the job advertisement. The obscure job descriptions may result in application of unsuitable candidates that can cause candidate rejection and time consuming. In this paper we proposed a text analytics technique to extract users’ comments from social media on job advertisement. The result is then displayed in a geotagged map that can reveal the density of job availability based on geographical location. The job seekers can easily observe and select their desired job location. The initial system shows potential of the inclusion of the proposed approach in job advertisement websites. In comparison to other job searching websites, this system can provide additional information on public view about the advertised job obtained from the social media text analytics. It is hoped that the proposed system can tailor the job advertisements to the need of the jobseeker and making the job application more relevant hence reducing the potential employers’ processing time